Chemokines in vascular remodeling - Schober, Andreas; Zernecke, Alma (Thrombosis and Haemostasis, 2007)
The arterial vessel wall response to a variety of injuries consists in structural changes, which can result in luminal narrowing and aggravation of the underlying disease.This arterial remodeling is characterized by neointima formation and medial thickening, inflammatory cell recruitment and endothelial dysfunction. Chemokines and the corresponding receptors have been shown to participate at every step of the remodeling process.The monocyte chemotactic protein (MCP)-1/CC motif receptor 2 (CCR2) axis induces monocyte infiltration of the injured vessel wall and can stimulate proliferation of smooth muscle cells (SMCs) in models of restenosis, cardiac allograft vasculopathy (CAV), pulmonary hypertension, and systemic hypertension. In contrast, stromal cell-derived factor (SDF)-1α and its receptor CXC motif receptor 4 (CXCR4) are centrally involved in the neointimal recruitment of SMC progenitor cells (SPCs), presumably in response to SMC apoptosis, in restenosis and CAV.The RANTES (Regulated upon activation, normally T-cell expressed,and presumably secreted) receptors CC motif receptor 1 (CCR1) and CC motif receptor 5 (CCR5) affect intimal monocyte infiltration and neointimal growth, which could be due to the deposition of platelet-derived RANTES on activated endothelial cells. Fractalkine is expressed on neointimal SMCs and thus mediates the arrest of monocytes. Interestingly, reendothelialization of injured vessels appears to primarily depend on CXC motif ligand 1 (CXCL1).These chemokine effects form a complex network, which operates in all mechanisms of vascular remodeling.The detailed understanding of the function of the chemokine network in the remodeling process may allow specific disease intervention.
Keywords: Chemokines; leukocyte trafficking/recruitment; vascular remodeling; smooth muscle cells; stem cells